Encephaloduroarteriosynangiosis Averts Stroke in Atherosclerotic Patients With Border-Zone Infarct: Post Hoc Analysis From a Performance Criterion Phase II Trial. Issue 4 (19th January 2021) - Quintero-Consuegra, Miguel D; Toscano, Juan F; Babadjouni, Robin; Nisson, Peyton; Kayyali, Mohammad N; Chang, Daniel; Almallouhi, Eyad; Saver, Jeffrey L; Gonzalez, Nestor R
Abstract: BACKGROUND: Intracranial atherosclerotic disease (ICAD) is one of the leading causes of stroke worldwide. Patients with ICAD who initially present with ischemia in border-zone areas and undergo intensive medical management (IMM) have the highest recurrence rates (37% at 1 yr) because of association with hemodynamic failure and poor collaterals. OBJECTIVE: To evaluate the effect of encephaloduroarteriosynagiosis (EDAS) on stroke recurrence in patients with ICAD and border-zone stroke (BDZS) at presentation. METHODS: A phase II clinical trial of EDAS revascularization for symptomatic ICAD failing medical management (EDAS Revascularization for Symptomatic Intracranial Atherosclerosis Steno-occlusive [ERSIAS]) was recently concluded. We analyze the outcomes of the subgroup of patients with BDZS at presentation treated with EDAS vs the previously reported Stenting versus Aggressive Medical Management for Preventing Recurrent stroke in Intracranial Stenosis (SAMMPRIS) IMM subgroup with BDZS at presentation. RESULTS: Of 52 patients included in the ERSIAS trial, 35 presented with strokes at baseline, and 28 had a BDZ pattern, including 15 (54%) with exclusive BDZS and 13 (46%) with mixed patterns (BDZ plus other distribution). Three of the 28 (10.7%) had recurrent strokes up to a median follow-up of 24 months. The rate of recurrent stroke in ICAD patients with BDZS at presentation after EDAS was significantly lower than the rate reported in the SAMMPRIS IMM subgroup with BDZS at presentation (10.7% vs 37% P = .004, 95% CI = 0.037-0.27). CONCLUSION: ICAD patients with BDZS at presentation have lower rates of recurrent stroke after EDAS surgery than those reported with medical management in the SAMMPRIS trial. These results support further investigation of EDAS in a randomized clinical trial. Graphical Abstract: